'We were there too': There is much to learn from embedding auto/biography in the knowing and doing of prison research. Issue 2 (December 2017) - Brown, Geraldine; Bos, Elizabeth
Within the social sciences, there is a wealth of literature that examines the challenges and ethical dilemmas encountered by researchers in conceptualising, conducting and understanding their research. In this article, we share our reflections on experiences we encountered carrying out a qualitative evaluation of a prison gardening intervention with male substance misusing prisoners. Our aim is to suggest that there is much we can gain when researchers engage in a process of reflexivity, which includes consideration to the intersection of identity of the researcher, the researched and the forces of various kinds, operating upon and within such situations. As such, here we share our fieldwork experiences and shed light on how, for us, the evaluation was a subjective, power-laden, emotional, embodied experience. We highlight how a human geographer and a sociologist working as part of a multidisciplinary evaluation team encountered issues associated with choices in terms of how we conduct our work, the emotional labour expended and how we had to assume both chosen and imposed identities. We have been challenged to consider and reflect upon aspects of gender, class, age and professional status throughout our research experience, with the 'researched' and between the 'researchers'. Finally, we suggest that embarking on qualitative research in a prison setting is an outcome of complex negotiations, but in theorising our subjectivities is a means of illuminating issues that often remain invisible within prison research.